1970
DOI: 10.1097/00000658-197007000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Urological Complications in 216 Human Recipients of Renal Transplants

Abstract: FOR the most part, the surgical technics of kidney transplantation have been standardized. 3 , 8, 10, 11,11,25 The least satisfactory aspect of this operation is provision of urinary drainage as will be demonstrated by an analysis of the urologic complications encountered in 216 consecutive recipients of renal grafts at the Colorado General and Denver Veterans Administration Hospitals.The Denver series is a useful one with which to study the attributes and deficiencies of urinary drainage procedures, not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
8

Year Published

1971
1971
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(54 citation statements)
references
References 21 publications
0
46
0
8
Order By: Relevance
“…In our study, no patient died because of urologic complications, and we showed considerably good results (urinary leak rate was 2.5%, stenosis rate was 5%) compared with the literature (2.5%-25%). [12][13][14][15] Decreased blood supply to the donor ureter and faulty surgical techniques are the main causes of urologic complications; however, other problems, such as immunosuppressive drugs and rejections, can cause late obstruction. Although low-dose steroid protocols and meticulous operative techniques tend to reduce incidence or urologic complication, 10 poor ureteral vascularization owing to increased use of expanded criteria donors, especially older individuals, tend to increase this rate.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, no patient died because of urologic complications, and we showed considerably good results (urinary leak rate was 2.5%, stenosis rate was 5%) compared with the literature (2.5%-25%). [12][13][14][15] Decreased blood supply to the donor ureter and faulty surgical techniques are the main causes of urologic complications; however, other problems, such as immunosuppressive drugs and rejections, can cause late obstruction. Although low-dose steroid protocols and meticulous operative techniques tend to reduce incidence or urologic complication, 10 poor ureteral vascularization owing to increased use of expanded criteria donors, especially older individuals, tend to increase this rate.…”
Section: Discussionmentioning
confidence: 99%
“…Evolution to this technique has covered some 50 years of surgical progress. The ureteral anastomosis of kidney transplantation has historically been plagued by high complication rates, with early studies reporting mortality as high as 50% in those patients developing a urinary leak (1)(2)(3). Other commonly reported urinary complications include ureteral necrosis, stenosis and obstruction, clinically significant posttransplant hematuria, vesicoureteral reflux and infection (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Recent incidence of urological complications is between 2.5% to 12.5% 13 , which is significantly lower than the 25% reported in the early days of renal transplantation. 14 There are many factors responsible for urological complications but the two most important factors are the blood supply of distal ureter and the technique of reimplantation. 15 The preservation of the blood supply of the distal ureter by careful preservation of the periureteric fat and the appropriate length of the ureter prevents the necrosis of distal ureter.…”
Section: Discussionmentioning
confidence: 99%